Problems in plan Implementation. (Delhi, 1964)
The aim of this booklet is to promote a better apprecia tion of the problems of implementing the Third Five Year Plan, and of its achievements. Part I of the booklet carries extracts from The Third Plan: Mid-Term Appraisal placed by the Government before Parliament on November 25, 1963. Part II comprises articles published in the Plan Implementation Special Number of Yojana dated October 13, 1963. The article "Mineral Resources" by Dr. M. S. Krishnan appeared in the October 27, 1963, issue of the journal.
Keywords: Economic development